Effect of Chitosan and Naringin on Enteric Methane Emissions in Crossbred Heifers Fed Tropical Grass - Jiménez Ocampo, Rafael; Montoya Flores, María Denisse; Herrera Torres, Esperanza; Pámanes-Carrasco, Gerardo; Arceo Castillo, Jeyder Israel; Valencia Salazar, Sara Stephanie; Arango, Jacobo; Aguilar-Pérez, Carlos Fernando; Ramírez Avilés, Luis; Solorio-Sánchez, Francisco Javier; Piñeiro Vázquez, Ángel Trinidad; Ku-Vera, Juan Carlos (MDPI, 2021)
Simple Summary